CONNOTATIVE MEANING AS PART OF THE SEMANTIC STRUCTURE - Khaydarov A. A.; Aminova Zarina Raimovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article is devoted to the consideration of the connotative meaning as part of the semantic structure of the word along with the subject-logical and grammatical macro-components. The study of connotation is proposed to be carried out taking into account the distinction between speech and language connotations, as well as taking into account the concept of linguistic personality.